PERKEMBANGAN AWAL SISTEM KARDIOVASKULAR EMBRIO AYAM GALUR HIGHLAND DIBAWAH PENGARUH DOSIS SUBLETAL PARAKUAT - Yetty Yusri Gani; Dyah Retnosari; Nining Ratningsih (Universitas Padjadjaran, 2003)
The research was carried out in order to determine the effect of paraquat on the early development of chick embryos. Doses of paraquat 0, 0.1, 0.25, 0.55, or 1.25 mg/egg paraquat were administered to the unincubated Highland chick embryos and examined for cardiovascular abnormalities on 96 hours of incubation. The result showed no malformation in heart, but aortic arch development occurred. Nevertheless, doses 0.55 and 1.25 mg/egg of paraquat caused a highly significant increase (p<0.01) in the extraembryonic vessels malformations. All the administered doses did not significantly caused intraembryonic vessels malformations. Doses 0.55 and 1.25 mg/egg of paraquat also caused a highly significant increase (p<0.01) in both frequency of erythrocytes abnormalities and the micronucleated erythrocytes. This experiment represented a significant increase in extraembryonic vessels malformations, abnormalities and mutation level of erythrocytes due to the administered doses.